Constitutional Rules and Fiscal Policy Outcomes - Persson, Torsten; Tabellini, Guido (American Economic Review, 2004)
We investigate the effect of electoral rules and forms of government on fiscal policy outcomes in a large sample of democracies. We rely on different estimation methods to address prospective problems of statistical inference, due to nonrandom selection of these constitutional rules. The findings are consistent with our theoretical priors: presidential regimes induce smaller governments than parliamentary democracies, while majoritarian elections lead to smaller governments and smaller welfare programs than proportional elections.